Znamenskaya Church in Tverskaya Street and Some Peculiar Features of Interpretation of Medieval Russian Forms in St. Petersburg Architecture of the Early 20th Century - Titorenko, Natalia G. (Actual Problems of Theory and History of Art, 2013)
This article is devoted to the revival of Old-Russian forms in Petersburg architecture of the early 20th c. on the example of the Znamenskaya church in Tverskaya street. The author’s attention is drawn to the comparison of the individual architectural forms characteristic of the Znamenskaya church, with their possible Old-Russian counterparts.
Keywords: Znamenskaya church in Tverskaya street; D.A. Kryzhanovsky; St. Petersburg architecture of early 20th c